1997
DOI: 10.3354/meps146009
|View full text |Cite
|
Sign up to set email alerts
|

Substrate selection and use of protective cover by juvenile Atlantic cod Gadus morhua in inshore waters of Newfoundland

Abstract: We investigated the habitat preferences and use of cover of 1 to 4 yr old juvenile cod G a d u s rnorhua in the inshore waters (18 to 150 m depth) of Placentia Bay, Newfoundland, Canada. using deep sea submersibles (PISCES IV & SDL-1) in April 1995. We analysed a total of 32 h of 'onbottom' videotape, audiotape, and ivritten records from 9 daylight dives and l nlght dive. Habitat types were characterised by depth, substrate particle size, bathymetric relief, and the presence or absence of macroalgae. Juvenile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 21 publications
0
66
2
Order By: Relevance
“…Juvenile cod have also been shown to use the interstitial spaces of less complex mineral substrates such as cobble and gravel for predator avoidance (e.g. Lough et al 1989, Gregory & Anderson 1997. However, the substrate particle size at the sand sites was ca.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Juvenile cod have also been shown to use the interstitial spaces of less complex mineral substrates such as cobble and gravel for predator avoidance (e.g. Lough et al 1989, Gregory & Anderson 1997. However, the substrate particle size at the sand sites was ca.…”
Section: Discussionmentioning
confidence: 97%
“…Grant & Brown (1998a) report limited movement of juvenile cod between sites following settlement in nearshore areas, suggesting there were large sections of unfavourable habitat between sampling sites. Age 0 juvenile cod are restricted to shallow, nearshore habitat such as eelgrass, possibly due to increased predation with depth (Linehan et al 2001) and reduced habitat complexity beyond the littoral zone (Gregory & Anderson 1997). Mark-recapture studies conducted between areas of varying habitat and depth may therefore misrepresent the capacity of movement in juvenile cod.…”
Section: Discussionmentioning
confidence: 99%
“…Nakamura, 1985). A number of fish species, including codfishes, wrasses, and flatfishes have been shown to associate with high relief structures of comparably low complexity during parts or most of their life cycles (Gregory and Anderson, 1997;Light and Jones, 1997;Stanley et al, 2002;Johnson et al, 2003;Cote et al, 2004;Wilhelmsson et al, 2006b). …”
Section: Discussionmentioning
confidence: 99%
“…Modifying the risk of predation for an individual involves searching out areas that reduce a predator's ability to locate and capture prey (Giske et al 1998). A number of studies have demonstrated that survivorship of juvenile Atlantic cod Gadus morhua is related to habitat structure, which may at least partly explain the slow recovery of the stock after its collapse (Lough et al 1989, Gotceitas & Brown 1993, Tupper & Boutilier 1995, Gregory & Anderson 1997, Lindholm et al 1999). This implies that we need to understand the behaviour and ecology of fish over various space and time scales, as well as their recruitment dynamics, to sustainably manage populations (Bailey 1994).…”
Section: Discussionmentioning
confidence: 99%